Penerapan Prinsip-Prinsip Good Governance Dalam Meningkatkan Kualitas Pelayanan Publik Pada Kantor Badan Pendapatan Daerah Kota Bogor - Lionandiva, Guntur; Triandi, Triandi (Institut Bisnis dan Informatika Kesatuan, 2022)
This research was conducted because of the lack of application of the principles of good governance carried out by public service providers. This study aims to determine whether the application of the principles of transparency, accountability, and participation as an element of good governance has an effect on improving the quality of public services at the Bogor City Regional Revenue Agency. Determination of the sample in this study is by distributing questionnaires where the questionnaire must be filled out by 100 respondents and after that the data obtained will be processed by SPSS 25 and the analysis technique used is multiple linear regression. The results of the study based on the measurement of research instruments show that the application of the principles of good governance has been carried out very well by BAPENDA Bogor. The results of the study based on the significant value and the comparison of t arithmetic with t table show that the principle of transparency has a significant effect on the quality of public services where the more transparent a government will increase public trust and the quality of public services. Accountability has no significant effect on the quality of public services due to limited public perception in understanding the principle of accountability. The principle of participation has no significant effect on the quality of public services due to whether or not the community is active in providing criticism and suggestions to the government, the policies taken by the government seem to pay less attention to people's aspirations. From the results of the significant test and the calculated F compared to the F table, it shows that the principles of transparency, accountability, and participation as elements of good governance have a simultaneous effect on the quality of public services, which if these three principles are carried out properly it will better guarantee a public service performance. so that the better the application of the principles of transparency, accountability, and participation, the better the performance of a public service so that the quality of public services will also improve. Keywords: transparency, accountability, participation, good governance, quality of public services